Church-based social interactions and psychotic experiences among Black Americans: findings from the National Survey of American Life. Issue 2 (7th February 2019) - Oh, Hans; Waldman, Kyle; Lloyd, Donald; Lincoln, Karen
ABSTRACT: Religious attendance has generally been salutary for mental health, though recent evidence suggests that church attendance has no significant relation with psychotic experiences. This study will examine how various types of church-based social interactions might be related to psychotic experiences. We analysed data from the National Survey of American Life –a representative sample of Black Americans in the United States –and used multivariable logistic regression to examine associations between seven church-based social interaction variables and lifetime psychotic experiences. In separate models, church attendance, church member interaction, and closeness to church members were not significantly associated with psychotic experiences, while greater emotional support, negative social interactions, providing help to other church members and receiving help from fellow church members were associated with increased odds of reporting psychotic experiences. But in a fully adjusted model including all church-based social interaction variables, only negative church interactions and giving help to church members were significantly associated with psychotic experiences. Church-based social interactions did not protect against psychotic experiences, and in some cases increased risk. Future studies should explore why the deleterious aspects of social interactions prevail over the beneficial ones.